Calibrating the human instrument: understanding the interviewing experience of novice qualitative researchers - Peredaryenko, Margarita Sergeevna; Krauss, Steven Eric (Nova Southeastern University, 2013)
Scientific instruments often undergo calibration to ensure that they will produce results that meet or exceed defined criteria within a specified degree of confidence. Such calibration almost always refers to mechanical instruments, those used primarily in the physical sciences. Rarely is the notion of calibration used in relation to the social and human sciences, especially in the context of qualitative research where the human being is the main research instrument. The focus of this study was to explore the experiences of novice human instruments undergoing a process similar to that of calibration. In doing so, we studied how novice qualitative researchers perceived themselves as the research instrument in the process of their first qualitative interviewing experiences. The findings from interviews with four such novices were that their initial calibration gravitated towards one of two states — being “researcher - centered” or “informant - centered .” Their proximity to either of these two states was determined by how they identified with each of four dimensions: (a) where the knowledge of the phenomenon under study lies; (b) what kind of response the researcher received from his/her informants; (c) what kind of information the researcher is looking for; and (d) what kind of information the researcher eventually receives. The middle position on the continuum of states between researcher - centeredness and informant - centeredness is discussed in relation to complexity theory.